Dampak pabrik terhadap eksistensi petani di Desa Pendosawalan Kecamatan Kalinyamatan Kabupaten Jepara - Afriyanto, Jefri; Wijaya, Atika (Environmental, Social, Governance and Sustainable Business, 2024)
Background: This study discusses the impact of the garment factory on the existence of farmers in Pendosawalan Village. The factory in Pendosawalan Village has an influence on the condition of farmers in Pendosawalan Village. This study aims to: 1) determine the development of factories in Pendosawalan village, 2) find out the impact of the existence of factories on the people of Pendosawalan village, Kalinyamatan district, Jepara district, 3) find out the impact of factories on the sustainability of agriculture in Pendosawalan village. , Kalinyamatan District, Jepara Regency. Methods: The theory used in this study is the theory of rational choice from James S. Coleman. This study used qualitative research methods. Data collection techniques were carried out by observation, interviews, and documentation. Findings: The factory is able to absorb labor from the people of Pendosawalan Village and outside Pendosawalan Village. Conclusion: Based on the results of the research conducted, it is known that: 1) The existence of PT. Kanindo Makmur Jaya in Pendosawalan Village has environmental and economic impacts. 2) Environmental impacts caused by factories include reduced agricultural land, pollution of irrigation channels and interruption of irrigation channels. 3) Development of PT. Kanindo Makmur Jaya in Pendosawalan Village benefits the community in the economic aspect.